Increased nuclear DNA damage precedes mitochondrial dysfunction in peripheral blood mononuclear cells from Huntington's disease patients - Askeland, Georgina; Dosoudilova, Zaneta; Rodinova, Marie; Klempir, Jiri; Liskova, Irena; Kuśnierczyk, Anna; Bjørås, Magnar; Nesse, Gaute; Klungland, Arne; Hansikova, Hana; Eide, Lars (Scientific reports, 2018)
Huntington's disease (HD) is a progressive neurodegenerative disorder primarily affecting the basal ganglia and is caused by expanded CAG repeats in the huntingtin gene. Except for CAG sizing, mitochondrial and nuclear DNA (mtDNA and nDNA) parameters have not yet proven to be representative biomarkers for disease and future therapy. Here, we identified a general suppression of genes associated with aerobic metabolism in peripheral blood mononuclear cells (PBMCs) from HD patients compared to controls. In HD, the complex II subunit SDHB was lowered although not sufficiently to affect complex II activity. Nevertheless, we found decreased level of factors associated with mitochondrial biogenesis and an associated dampening of the mitochondrial DNA damage frequency in HD, implying an early defect in mitochondrial activity. In contrast to mtDNA, nDNA from HD patients was four-fold more modified than controls and demonstrated that nDNA integrity is severely reduced in HD. Interestingly, the level of nDNA damage correlated inversely with the total functional capacity (TFC) score; an established functional score of HD. Our data show that PBMCs are a promising source to monitor HD progression and highlights nDNA damage and diverging mitochondrial and nuclear genome responses representing early cellular impairments in HD.
Keywords: Young Adult; mitochondriální DNA; DNA, Mitochondrial; poškození DNA; Mitochondria; Male; DNA Damage; mladý dospělý; leukocyty mononukleární; nestabilita genomu; Huntingtonova nemoc; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Genomic Instability; Huntington Disease; Leukocytes, Mononuclear; lidé; ženské pohlaví; studie případů a kontrol; Humans; Female; lidé středního věku; mitochondrie; Middle Aged